1999
DOI: 10.1083/jcb.144.4.657
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-dependent Plus- and Minus End–directed Motilities Are Competing Processes for Nuclear Targeting of Adenovirus

Abstract: Adenovirus (Ad) enters target cells by receptor-mediated endocytosis, escapes to the cytosol, and then delivers its DNA genome into the nucleus. Here we analyzed the trafficking of fluorophore-tagged viruses in HeLa and TC7 cells by time-lapse microscopy. Our results show that native or taxol-stabilized microtubules (MTs) support alternating minus- and plus end–directed movements of cytosolic virus with elementary speeds up to 2.6 μm/s. No directed movement was observed in nocodazole-treated cells. Switching b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
426
3
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 410 publications
(460 citation statements)
references
References 71 publications
(119 reference statements)
24
426
3
7
Order By: Relevance
“…2). This was observed for Reovirus, Adenovirus, HSV, influenza virus and HIV 5,[42][43][44][45] . Viral transport is often highly regulated as with, for example, HSV in neurons.…”
Section: Viral Transportmentioning
confidence: 57%
See 2 more Smart Citations
“…2). This was observed for Reovirus, Adenovirus, HSV, influenza virus and HIV 5,[42][43][44][45] . Viral transport is often highly regulated as with, for example, HSV in neurons.…”
Section: Viral Transportmentioning
confidence: 57%
“…Important signalling events might occur during viral transport. During its dyneindependent motion along microtubules, Adenoviruses transiently activate distinct signalling cascades, such as cAMP dependent protein kinase A, p38/mitogen activated protein kinase (MAPK) and the downstream MAPK activated protein kinase 2, to balance nuclear targeting and enhance infection 42,54 .…”
Section: Viral Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Ad capsid proteins are known to interact with MTs and cytoplasmic dynein during transit to the nucleus. 40,41 We have previously shown that inhibition of cytoplasmic dynein activity in lacrimal acini severely impairs the formation of rab3D-enriched secretory vesicles. 27 However, direct dynein inhibition also prevents the recruitment of VAMP2-enriched secretory transport vesicles to the apical membrane in response to CCH, while this response is unaffected by Ad (data not shown), suggesting that some dynein-mediated traffic to the apical membrane can proceed normally in Ad-treated acini.…”
Section: Discussionmentioning
confidence: 99%
“…Other pathways have, however, been suggested, 40,41 and adenoviral particles have been observed in vesicles without clathrin coating and in macropinosomes. The enhanced gene transfer after photochemical treatment could be due to the release of the viral particles from any of these vesicles.…”
Section: Discussionmentioning
confidence: 99%